A Case of Life-Threatening Contralateral Tension Pneumothorax during Video-Assisted Thoracic Surgery in a Patient with Retrosternal Goiter - Nimitha Prasad; Sucheta S. Gaiwal (Annals of Cardiac Anaesthesia)
We report a case of a 74-year-old female with a retrosternal goiter undergoing video-assisted thoracic surgery (VATS) for a left lung lower lobectomy, necessitating one-lung ventilation (OLV). We encountered a highly unusual complication: contralateral tension pneumothorax. Forty-five minutes into the surgical procedure, a sudden cardiovascular collapse occurred. After confirming the correct positioning of the double-lumen tube and excluding mediastinal mass syndrome (MMS), tension pneumothorax was suspected. Immediate needle decompression followed by right chest tube thoracostomy resulted in a successful patient outcome. This case highlights the importance of maintaining a high index of suspicion for contralateral tension pneumothorax in patients with sudden cardiovascular collapse during OLV.